ON SCIENTIFIC AND MEDICAL PERSONNEL TRAINING AT V.I. SHUMAKOV FEDERAL RESEARCH CENTER OF TRANSPLANTOLOGY AND ARTIFICIAL ORGANS - статья Редакционная (Вестник трансплантологии и искусственных органов)
.